Solution-processed, binder-free pristine Ti3C2Tx MXene electrodes enabled by MAI passivation for high-performance, scalable perovskite solar cells - Harit Chunlim; Manopat Depijan; Kasempong Srisawad; Tanawut Meekati; Duangmanee Wongratanaphisan; Pipat Ruankham; Pongsakorn Kanjanaboos; Pasit Pakawatpanurut (Applied Surface Science Advances)
While carbon electrodes offer a cost-effective option for perovskite solar cells (PSCs), their efficiency is often compromised by the insulating polymer binders required. Addressing this limitation, we demonstrate a polymer binder-free electrode using pristine Ti3C2Tx MXene, applied directly onto the perovskite via a simple solution-processing technique. A major obstacle emerged: the direct interface between untreated, hydrophilic Ti3C2Tx and the perovskite proved unstable, causing rapid degradation. We resolved this critical issue by introducing a novel methylammonium iodide (MAI) surface treatment for Ti3C2Tx prior to deposition. This passivation strategy proved essential, stabilizing the interface by neutralizing reactive surface groups. PSCs utilizing these MAI-treated, binder-free Ti3C2Tx electrodes achieved 13.8 % power conversion efficiency, substantially exceeding carbon controls (10.7 %), primarily due to a significantly enhanced fill factor (75.2 % vs 58.2 %) and low sheet resistance. Furthermore, demonstrating practical potential, these MXene electrodes maintain performance better than carbon when the active area is scaled up. Although encapsulation is required to protect the hydrophilic MXene and ensure long-term stability (>360 h) in ambient conditions, this work charts an effective course for developing highly conductive, scalable, binder-free electrodes for advanced PSCs.